Angiotensin II Type I Receptor Agonistic Autoantibody Induces Podocyte Injury via Activation of the TRPC6- Calcium/Calcineurin Pathway in Pre-Eclampsia - Yu, Ying; Zhang, Lihong; Xu, Guang; Wu, Zhenghong; Li, Qian; Gu, Yong; Niu, Jianying (Kidney & blood pressure research, 2018)
Background/Aims: Angiotensin II type I receptor agonistic autoantibody (AT1-AA) is closely related to pre-eclampsia, which is characterized by proteinuria and hypertension. AT1-AA has been shown to enhance the effect of AngII in pre-eclampsia, such as production of endothelin-1, activation of ROS, and vasoconstriction, which are considered to be associated with hypertension; however, whether or not AT1-AA participates in podocyte damage leading to the generation of proteinuria has not been reported. In this study we investigated the role of pre-eclamptic serum AT1-AA on podocytes and the mechanism underlying the generation of proteinuria. Methods: The levels of AT1-AA isolated from pre-eclamptic sera were determined by an enzyme-linked immunosorbent assay. Human podocytes were cultured in vitro and treated with various concentrations of AT1-AA. Whether or not an ERK1/2 inhibitor and TRPC6 siRNA inhibit the effect of AT1-AA on podocytes was determined. Western blot was used to detect the expression of podocyte-specific proteins (nephrin, synaptopodin, and podocin) and the phosphorylation of ERK1/2 and TRPC6. The arrangement of F-actin was observed by immunofluorescence. A Calcineurin Cellular Activity Assay Kit was used to detect calcineurin activity. Changes in the intracellular Ca 2+ concentration was determined by confocal laser. Results: AT1-AA induced a decrease in podocyte-specific protein expression and calcineurin activity and increased expression of p-ERK1/2 and TRPC6 protein and the intracellular Ca 2+ concentration. Immunofluorescence revealed rearrangement of F-actin. PD98059, an inhibitor of ERK1/2, and TRPC6 siRNA attenuated the decreased expression of podocyte-specific proteins and decreased intracellular Ca 2+ concentration. The expression of TRPC6 was reduced following the addition of ERK1/2 inhibitor. Conclusion: AT1-AA induced podocyte damage in a dose-dependent manner. The underlying mechanism might involve activation of the TRPC6 –calcium/calcineurin pathway. This study provides new details regarding podocyte injury and the mechanism underlying the generation of proteinuria in pre-eclampsia.